Enantioselective synthesis of γ-chiral amides via copper-catalyzed reductive relay hydroaminocarbonylation - Yang Yuan; Youcan Zhang; Xiao-Feng Wu (Nature Communications, 2024)
Abstract Chiral amides are common and effective structural motifs found in many pharmaceuticals and biologically active molecules. Despite their importance, existing synthetic methods are predominantly employed for the synthesis of α-amides and β-amides. The synthesis of remote chiral amides, characterized by distal stereocenters, typically requires intricate synthetic steps conducted under demanding conditions. Here, we present a general procedure for the copper-catalyzed enantioselective synthesis of γ-chiral amides, employing a reductive relay hydroaminocarbonylation strategy with trisubstituted allylic benzoates and hydroxylamine electrophiles. This approach demonstrates a wide substrate scope with excellent enantioselectivity and regioselectivity, thus providing access to challenging enantioenriched γ-chiral amides.